2019
DOI: 10.5530/ptb.2019.5.24
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antimicrobial Medications Consumption in Inpatient Units at North West (Tabuk) Region Hospitals, Saudi Arabia

Abstract: Background: This article aims to explore antimicrobial medication consumption and related cost among different age groups in inpatient units at North West Region Hospitals, Ministry of Health, and Saudi Arabia. Objectives: To explore the selected antimicrobial medication consumption in inpatient units at North West Region Hospitals, Ministry of Health, Saudi Arabia. To increase the awareness of anti microbial medication consumption side effect. Methods: It is a 9month study about antimicrobial drug use by inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…[3][4][5] The infection control starting from use necessary infection control measures of hand wishing techniques, using sanitizer or chemical disinfectant and isolation of infected cases, or isolated of cities form to enter and outer from it [3][4][5] Besides, several studies showed resistance bugs locally and overall the world, [6][7][8][9][10] and high consumption of broad spectrum of antibiotics and increased economic burden at emergency, inpatient ward, critical care and ambulatory care services. [11][12][13][14][15][16] Moreover, the pharmacy services consisted of m preparation, distribution and dispensing parenteral or ophthalmic medications. Those pharmacy units need bright places and preparation of sterile products.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The infection control starting from use necessary infection control measures of hand wishing techniques, using sanitizer or chemical disinfectant and isolation of infected cases, or isolated of cities form to enter and outer from it [3][4][5] Besides, several studies showed resistance bugs locally and overall the world, [6][7][8][9][10] and high consumption of broad spectrum of antibiotics and increased economic burden at emergency, inpatient ward, critical care and ambulatory care services. [11][12][13][14][15][16] Moreover, the pharmacy services consisted of m preparation, distribution and dispensing parenteral or ophthalmic medications. Those pharmacy units need bright places and preparation of sterile products.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are widely used locally and internationally. [1][2][3][4] There is a high consumption of antibiotics, which is the Kingdom of Saudi Arabia, especially in adult patients. Besides, antibiotics consumption was high in neonates and pediatrics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Parental antibiotics most consumption at critical care and inpatient wards units, while the oral antibiotics are widely used at ambulatory care and emergency services. [1][2][3][4] The most antibiotics consumption was a very broad spectrum with the subsequent high economic burden on the healthcare system. [3,4] The parenteral antibiotics need preparation in multiple diluent solutions and various concentration based on local or international guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] The both programs implemented to meet the high consumption of parenteral antibiotics with the high-cost burden on the healthcare system at. [4,5] The IV admixture program developed adult's medication dilution manual as guidelines for the preparation of parenteral medications and including antibiotics among them to prevent antibiotics related problems. [2] Beside, one of the essential factor to prevent antibiotics preparation errors for adults was the standardized antibiotics intravenous infusions.…”
Section: Introductionmentioning
confidence: 99%